Pengaruh Fikih Muamalah, Kompensasi dan Religiositas terhadap Perilaku Curang - Artika , Artika; Faisal, Yusuf (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2024)
This research aims to obtain empirical evidence about the influence of muamalah fiqh, compensation and religiosity on fraudulent behaviour. This research uses a quantitative type of research. This research was conducted using a questionnaire distributed to lecturers and practitioners who are members of the Ikatan Ahli Ekonomi Islam (IAEI), Masyarakat Ekonomi Syariah (MES), Forum Dosen Ekonomi dan Bisnis Islam (FORDEBI) and Ikatan Sarjana Ekonomi Indonesia (ISEI). Each questionnaire distributed contains 114 statements for respondents to answer. From the distribution of the questionnaire, 207 respondents provided answers from 22 regions. To get the results of this research, researchers used PLS SEM Version 3.0. The results of this study found that muamalah fiqh has a significant negative effect on fraudulent behaviour, compensation has a significant negative effect on fraudulent behaviour and religiosity has a significant negative effect on fraudulent behaviour. This research focuses on fraudulent behaviour, where this research is new research in discussing the relationship between muamalah fiqh and religiosity which is the basis of the character of the Rasulullah PBUH.